TUTOR'S OPINION TOWARDS SELF-EFFICACY IN PEDAGOGY - Liang Fu,; Adenan Ayob, (Journal of Islamic, Social, Economics and Development, 2023)
Tutor's personal traits are driving factors of the goals and behaviors at the institution. Self-Efficacy (SE) has been a primary concern for teachers and tutors at all levels. The literature indicates that tutors with low self-efficacy can negatively impact their future, adversely affecting the quality of teaching. The ability of tutors to handle the beliefs pertaining to handle the obligations, tasks, trends, and challenges in the context of professional development plays a pivotal role in acclaiming academic outcomes such as students' achievement as well as to provide motivation within the well-being of the working environment. This work assesses the opinion of tutors towards building their SE in the teaching pedagogy by conducting a comprehensive survey. This survey acts as a tool for understanding the gaps between the expectations and reality of the tutors, which is quintessential for further improvement. The key performance areas that need improvement are found from the study, which is in turn used to build an Intelligent Tutoring System from the perspective of aiding and supporting the tutors to improve student performance. As most of the elements are subjective in nature, the work also elaborates comprehensive assessment guidelines.